Magnetocrystalline anisotropy and exchange probed by high-field anomalous Hall effect in fully compensated half-metallic Mn2RuxGa thin films - Coey, John; Stamenov, Plamen; Rode, Karsten; Atcheson, Gwenael (My University, 2018)
Magnetotransport is investigated in thin films of the half-metallic ferrimagnet Mn2RuxGa in pulsed magnetic fields of up to 58 T. A nonvanishing Hall signal is observed over a broad temperature range, spanning the compensation temperature (155 K), where the net magnetic moment is strictly zero, the anomalous Hall conductivity is 6673Ω−1m−1, and the coercivity exceeds 9T. Molecular field modeling is used to determine the intra- and intersublattice exchange constants, and from the spin-flop transition we infer the anisotropy of the electrically active sublattice to be 216kJm−3 and predict the magnetic resonance frequencies. Exchange and anisotropy are comparable and hard-axis applied magnetic fields result in a tilting of the magnetic moments from their collinear ground state. Our analysis is applicable to collinear ferrimagnetic half-metal systems.
PUBLISHED
Keywords: Anomalous Hall effect; Exchange interaction; Ferrimagnetism; Magnetic anisotropy; Magnetotransport; Half-metals; FABRICATION; NANOSTRUCTURES; Nanotechnology; Physics